Gait Analysis Characteristics in Relapsed Clubfoot. Issue 2 (25th February 2023) - Bent, Melissa; Hauschild, Maia; Rethlefsen, Susan A.; Wren, Tishya A.L.; Liang, Adriana; Goldstein, Rachel Y.; Kay, Robert M.
Abstract : Background: Relapse rates of clubfoot deformity after initial correction range between 19% and 68% regardless of treatment approach. Most studies focus on relapse before age 4. Little research has focused on late clubfoot relapse. The purpose of this study was to compare the gait characteristics of children with late clubfoot relapse (age ≥5 y) following treatment with the Ponseti method only compared with intra-articular and extra-articular surgeries. Methods: A retrospective review was conducted of all patients with idiopathic clubfoot ≥5 years old who underwent computerized gait analysis for clubfoot relapse between 2001 and 2021. Joint range of motion, muscle strength, gait kinematics, and kinetics were compared among 3 groups based on prior clubfoot treatment: (1) Ponseti casting, (2) Extra-articular (EA) surgery, and (3) Intra-articular (IA) surgery. Results: Sixty-eight subjects (107 feet) were included (39 bilateral). Thirty-one percent of feet had been treated with Ponseti casting alone; 57% had IA surgery, and 12% had EA surgery. The average age when presenting with late relapse was 8.2 years, 9.0 years and 10.7 years for the Ponseti, and IA and EA groups, respectively. The IA group had greater passive dorsiflexion than the other 2 groups ( P <0.002), greater inversion weakness than the other 2 groups ( P <0.0001), greater dorsiflexion during the stance phase of gait compared with the Ponseti group ( P =0.001), and lower maximum power production at push-off compared with the other 2 groups ( P =0.009). Conclusion: Late relapse can occur after all types of clubfoot correction. Consistent with existing literature, patients who have undergone posteromedial release surgery have significantly greater plantarflexor weakness resulting in poorer plantarflexor moment and power production during gait. Level of Evidence: Level III, retrospective comparative study.